Celiac Disease: Prevalence in Bahawalpur Region and Pharmacological Evaluation of Natural Products in its Treatment (Medical Forum Monthly, 2024)
Objective: To assess the prevalence of celiac disease in Bahawalpur region Southern Punjab, Pakistan and to determine the pharmacological efficacy of kalonji seeds, olives and shawarma bread as its remedyStudy Design: Experimental studyPlace and Duration of Study: This study was conducted at the Bahawal Victoria Hospital Bahawalpur and private Gastroenterology and Hepatology clinics in Bahawalpur from January 2015 to June 2016.Materials and Methods: Both male and female patients visiting the Bahawal Victoria Hospital Bahawalpur and private Gastroenterology and Hepatology clinics in Bahawalpur, presenting with the symptoms of celiac disease such as chronic diarrhea, vomiting, abdominal pain and / or weight loss, were included in the study. A questionnaire consisting questions regarding demographic data, presenting complaints, associated illness, dietary habits and family history was applied and serology as well as small intestinal biopsy of the patients was performed by the expert gastroenterologist, and the patients with positive biopsy were designated as celiac. Out of 300 patients, only 203 agreed for biopsy and among these 203 patients, 150 were confirmed as celiac by biopsy reports. Celiac patients were divided into five main groups, each containing 30 according to their chief complaints. These groups were further divided into two sub-groups, A and B gluten free or control group and on gluten with remedy respectively. The group on gluten plus remedy was further divided into three sub-groups and each of them was given one of the natural edibles; i.e. kalonji seeds, olives and shawarma bread. The results were evaluated in terms of the recovery from chief complaints (diarrhea, vomiting, indigestion, abdominal pain and weight loss). The patients visited the consultant after 2nd,4th and 8th week of treatment to give the feedback of regimen.Results: Kalonji reduced diarrhea, nausea and abdominal pain in 75% of the patients and completely cured weight loss i.e. 100%. The efficacy of olives was also same. Shawarma bread reduce the symptoms of diarrhea upto100%, nausea, vomiting and abdominal pain 75%, indigestion and gas (50%), and weight loss in 100% of the patients.Conclusion: The symptoms of celiac disease can be reduced by bringing mild changes in the diet plan and addition of the edibles which have ability to prevent and reduce the symptoms of celiac disease.